2007
DOI: 10.1080/03639040601031890
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Design of a Highly Hygroscopic Drug (Pyridostigmine Bromide) for its Hygroscopic Character Improvement and Investigation of In Vitro/In Vivo Dissolution Properties

Abstract: Pyridostigmine bromide (PB) sustained-release (SR) pellets were developed by extrusion-spheronization and fluid-bed methods using Taguchi experimental and 2(3) full factorial design. In vitro studies, the 2(3) full factorial design was utilized to search for the optimal SR pellets with specific release rate at different time intervals (release percent of 2, 6, 12, and 24 hr were 6.24, 33.48, 75.18, and 95.26%, respectively) which followed a zero-order mechanism (n=0.93). The results of moisture absorption by K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Another modified release dosage forms of PB are Eudragit RS microparticles (Hegazy et al 2002), sustained released pellets (Huang et al 2007b), HPMC-based SR tablet (Huang et al 2007c), and prolonged release matrix tablet (Bolourchian et al 2012). Release rate of PB from these formulations was relatively high and 100 % of PB is released in less than 1 day (Huang et al 2007a, c;Hegazy et al 2002;Bolourchian et al 2012). Another modified release dosage of PB is poly (lactic acid) nanoparticles (NPs) (Tan et al 2012a), which releases most of the drug in the initial burst (50 % of PB was released in less than 1 h) followed by a very slow release over an extended period of time (72 h) (Tan et al 2012a).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another modified release dosage forms of PB are Eudragit RS microparticles (Hegazy et al 2002), sustained released pellets (Huang et al 2007b), HPMC-based SR tablet (Huang et al 2007c), and prolonged release matrix tablet (Bolourchian et al 2012). Release rate of PB from these formulations was relatively high and 100 % of PB is released in less than 1 day (Huang et al 2007a, c;Hegazy et al 2002;Bolourchian et al 2012). Another modified release dosage of PB is poly (lactic acid) nanoparticles (NPs) (Tan et al 2012a), which releases most of the drug in the initial burst (50 % of PB was released in less than 1 h) followed by a very slow release over an extended period of time (72 h) (Tan et al 2012a).…”
Section: Introductionmentioning
confidence: 96%
“…The nerve agents (NAs) used in chemical attacks cause disturbance to the synapse activity (Huang et al 2007a). Soman is one of the strongest of these NAs and treating Soman poisoning is difficult and dependent on timing (Huang et al 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Desired and reproducible results were achieved via microporous membrane coating using a soluble salt like sodium lauryl sulfate in the film coating solution (Elchidana and Deshpande, 1999). Huang et al have shown that the hygroscopic character of pyridostigmine bromide can be improved by coating process and the sustained-release pellets with specific release rate can be achieved by sustained-release coated pellets (Huang et al, 2007 Sustained-release matrix pellets Sustained-release matrix pellets are preferred to sustainedrelease coated pellets because of their ease of manufacture and in-process control. Theoretically, sustained-release matrix pellets can be formulated via the extrusion-spheronization process.…”
Section: Coated Pellets For Sustained Drug Deliverymentioning
confidence: 99%
“…Further alternatives may be derived 934 from pyridostigmine bromide, which rapidly transforms from solid 935 to liquid state under ambient conditions as a result of water anneal-936ing. To address this challenge, pyridostigmine bromide was encapsulated into Avicel pH 102 -a water-insoluble excipient -by 938 extrusion-spheronization and water uptake was prevented[152].Other studies deployed porous calcium silicate for formulation of 940 very hygroscopic drugs[153].These exemplarily selected formulation strategies addressing 942 the challenge of hygroscopicity might form interesting approaches943 to meet a potential increase in hygroscopicity of ILs as compared to944 crystalline, conventional salts of the APIs; however, further studies 945 are required to prove that these approaches are a reasonable concept for ILs. Beside, lipophilic counterions reduce the propensity for 947 water annealing of the API-counterion pair, however, likely affect 948 other pharmaceutical parameters such as the dissolution rate or 949 kinetic solubility.…”
mentioning
confidence: 99%
“…In most pharmaceutical 150 applications, ILs result from proton transfer (Brønsted) which is 151 sometimes specified as protic ILs [50,56]. API-ILs are usually syn- 152 thesized by metathesis reactions [43,57]. Typically the components 153 (API and counterion) are obtained as a certain salt, dissolved in a 154 suitable solvent (e.g.…”
mentioning
confidence: 99%